Cephalometric Measurements Of Non-Syndromic Oligodontia In Early Dental Age In A Japanese Population - Mayama H; Kuwajima Y; Da Silva JD; Khorashadi S; Lambert RF; Ishida Y; Ishikawa-Nagai S; Miura H; Satoh K (Dove Medical Press, 2019)
Hisayo Mayama,1 Yukinori Kuwajima,2 John D Da Silva,3 Shahrzad Khorashadi,2 R Frederick Lambert,2,4 Yoshiki Ishida,2 Shigemi Ishikawa-Nagai,2 Hiroyuki Miura,5 Kazuro Satoh1 1Division of Orthodontics, Department of Developmental Oral Health Science, School of Dentistry Iwate Medical University, Morioka, Iwate, Japan; 2Department of Oral Medicine, Immunity and Infection, Harvard School of Dental Medicine, Boston, MA, USA; 3Department of Restorative Dentistry and Biomaterials Science, Harvard School of Dental Medicine, Boston, MA, USA; 4Department of Health Policy and Management, Harvard T. H. Chan School of Public Health, Boston, MA, USA; 5Division of Dental Education, Department of Oral Medicine, School of Dentistry Iwate Medical University, Morioka, Iwate, JapanCorrespondence: Shigemi Ishikawa-NagaiHarvard School of Dental Medicine, 188 Longwood Avenue, Boston, MA, USATel +1-671-432-2928Fax +1-617-432-1897Email shigemi_nagai@hsdm.harvard.eduPurpose: Oligodontia significantly affects oral function and esthetics. Recognition of skeletal and dental patterns may aid in proper diagnosis and development of appropriate interventions. The aim of this study was to analyze skeletal and dental patterns for pre-adolescent patients with a diagnosis of oligodontia.Patients and methods: This study included 19 oligodontia patients (age: 9.5±1.3, Hellman’s developmental stage IIIA∼IIIB) along with a control group that comprised of 19 participants (age: 9.9±1.6) without any skeletal disharmony or congenitally missing teeth, with an Angle class I relationship and general crowding. Average cephalometric measurements among the oligodontia group were compared to the control group. The correlation between number of congenitally missing teeth (CMT) and each measurement was investigated. Skeletal measurements for both male and female patients in the oligodontia group and the control group were also compared.Results: No significant difference between the experimental and the control group was observed with respect to skeletal angular and linear measurements, except the gonial angle. Differences in dental pattern measurements were observed. The oligodontia group had significantly smaller Mo-Ms and Is-Mo than the control group (p<0.01). No correlation was detected between severity of oligodontia (number of CMT) and skeletal measurement except for SNB (R=−0.4). For females with oligodontia, Mo-Ms (eruption of maxillary first molar) and Is-Mo (mesial location of maxillary first molar) significantly differed from females in the control group (p<0.01). In contrast, no differences in Mo-Ms or Is-Mo were detected for male patients when oligodontia and control group were compared.Conclusion: Among pre-adolescent Japanese patients with oligodontia in Hellman’s developmental age IIIA∼IIIB, no significant differences in skeletal characteristics were established when compared to the control group. However, tooth position of maxillary first molars indicated smaller vertical descent and mesial shift, which may suggest weak maxillary vertical development.Keywords: non-syndromic oligodontia, congenitally missing teeth, craniofacial morphology, skeletal and dental pattern